1979
DOI: 10.1136/thx.34.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Serial pulmonary function tests in progressive systemic sclerosis.

Abstract: Serial pulmonary function tests were performed on nine patients with progressive systemic sclerosis over a mean period of ten years. Abnormality was seen to develop both early and late in the course of the disease, and the earliest abnormality observed was impairment of the transfer factor. Deterioration of some aspect of pulmonary function was noted in each case, evidence of restriction or air trapping being seen with equal frequency. Two patients died, both of causes unrelated to their pulmonary involvement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Moreover, among SSc patients, a negative correlation between TLCO/V A ratio and IL-4 levels (Spearman's coeffi cient = -0.46; p = 0.049) was evident. These fi ndings are coherent with the patho-physiology of the disease as regards the evolution of lung interstitial disease, where the TLCO parameter impairment appears as a validated indicator [29,30].…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, among SSc patients, a negative correlation between TLCO/V A ratio and IL-4 levels (Spearman's coeffi cient = -0.46; p = 0.049) was evident. These fi ndings are coherent with the patho-physiology of the disease as regards the evolution of lung interstitial disease, where the TLCO parameter impairment appears as a validated indicator [29,30].…”
Section: Discussionsupporting
confidence: 74%
“…In all cases there was perfect agreement between the two observers. Interstitial disease was located either in both lungs (patients 1, 4,5,6,9), predominantly in the upper lobes (patients 10 and 12), or in one upper lobe (patients 2 and 8). Patient 7 had bilateral axillary pleural thickening and centrilobular emphysema.…”
Section: Resultsmentioning
confidence: 99%
“…Small airway involvement in connective tissue disease is recognized especially in patients with RA or PSS, due to abnormalities in maximal midexpiratory flow rate (Collins et al 1976), flow volume curves with He-02 (Mountz et al 1984) or RV% (Guttadauria et al 1977;Bagg and Hughes 1979). Moreover, Hills et al (1979) indicated that if frequency dependence of dynamic compliance not accompanied by other abnormalities is found in RA patients, it may serve as a sign to detect early lung disease.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary function tests in these patients, especially in those with PSS and RA, often show restrictive and/or obstructive damage and, recently, small airway impairments (Collins et al 1976; Guttadauria et al 1977; Bagg and Hughes 1979;Hills et al 1979; Hunninghake and Fauci 1979; Begin et al 1982; Mountz et al 1984). Moreover, it has been reported that diffusing capacity is frequently decreased in MCTD patients (Sharp 1974(Sharp -1975Singsen et al 1977; Wiener-Kronish et al 1981; Sullivan et al 1984; Takasaki et al 1984; Derderian et al 1985; Prakash et al 1985), but there are few studies concerning the small airways.…”
mentioning
confidence: 99%